RETRACTED: Efficacy of BCG Vaccine and Role of Non Specific Sensitivity Due to Atypical Mycobacteria - Rajan R Patil; Krishnamurthy (Journal of Immunization, 2018)
This article has been retracted on December 28, 2018. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2577-137X.ji-25-5837) This paper attempts to summarizes possible reasons for BCG trial failure in India. It also lists out some of the important controversies and questions raised with regards to BCG trial in the context of Non Specific sensitivity. It emphasizes on the fact, that Tuberculin test does not accurately reflect individual’s responded immunologically to mycobacterium, it only indicates nature of immune response that has been elicited in an infected individual. The dynamics of tuberculin reaction needs to be understood through immunological considerations. Categorization of Tuberculin test results factoring in immunological considerations,will have great implication on the interpretation of tuberculin test and therefore on the estimation of annual risk of infection of tuberculosis.
Keywords: BCG Vaccine